Iron Deficiency Anemia (IDA) in Helicobacter Pylori Infection Patients: A Recent Study - Muhammad Mutaal Tahir, Muhammad Muaz Ayub, Muhammad Hasan Saeed, Muhammad Moiz Tahir, Muhammad Ali Tahir, Noor Tahir (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The study’s goal is to find out how common iron deficiency anaemia (IDA) is among those who have helicobacter pylori infection. Study Design: Cross-sectional/prospective study Place and Duration: Study was conducted at BHU 28 GB Jaranwala within duration of Aug 2021-Feb 2022. Methods: In all, there were 95 patients of all sexes, ranging in age from 20 to 70. Detailed information about each patient’s background and current residence was obtained through informed written permission from each one. It was found that every patient in this research had helicobacter pylori infection. Blood samples from the individuals were tested for serum iron, transferrin saturation, ferritin, and total iron-binding capacity. It is possible to identify H. pylori infection by the use of urea breath tests, stool antigen testing, fast urease testing, or histopathology. SPSS 22.0 was used to analyze all of the data in the study. Results: Among 95 patients, 57 (60%) were females and 38 (40%) were males. Mean age of the patients 33.41±8.44 years with mean BMI 25.09±7.31 kg/m2. Most of the cases were illiterate and were from rural areas. 55 (57.9%) cases had poor socio-economic status. Mean Hemoglobin level was 12.1±3.11 (g/dl) mean serum iron level was 49.5±8.31 (ug/dl) and mean serum ferritin level was 121.6±31.56 (ng per ml).Frequency of iron deficiency anemia was found in 40 (42.1%) patients. Conclusion: According to our findings, a substantial increase in iron deficiency anaemia was seen in helicobacter pylori-infected adults, the majority of whom were female.